Maternal perceptions and factors affecting Kangaroo mother care continuum at home: a descriptive study. (4th March 2018) - Raajashri, R.; Adhisivam, B.; Vishnu Bhat, B.; Palanivel, C.
Abstract: Objectives: To estimate the proportion of mothers who continued to practice Kangaroo mother care (KMC) at home and evaluate potential factors influencing this practice. Methods: This descriptive study was conducted in a tertiary care teaching hospital in south India. Mothers of preterm and low birth weight infants were trained in KMC during hospital stay. During follow up after 45 days, data regarding their perceptions and the practice of KMC at home and the factors influencing them were collected using questionnaires. Results: Among 200 mothers interviewed, 82.5% continued to practice KMC at home after discharge. The mean total duration of KMC was 30.2 days and average duration per day was 1.3 h. Support of family members was facilitatory in 70% and lack of privacy at home was hindering in 25%. Conclusion: After KMC training in hospital, majority of the post natal mothers were able to continue the practice satisfactorily at home despite hindering factors including lack of privacy. KMC training modules should emphasize continuing the practice at home after discharge and address the potential barriers for KMC continuum in the community.